2008
DOI: 10.1038/cgt.2008.4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lentivirus-mediated HIF-1α knockdown on hypoxia-related cisplatin resistance and their dependence on p53 status in fibrosarcoma cells

Abstract: Therapy targeting hypoxia-inducible factor-1 (HIF-1) to reverse the hypoxia-related drug resistance has received much interest. Despite a close interaction between HIF-1 and p53 and that p53 mutation is seen in 450% of tumors, whether HIF-1 silencing by targeted therapy depends on tumor p53 status remains unknown. Two isogenic fibrosarcoma cells HT1080 (wild-type p53) and HT1080-6TG (mutant p53) were transduced with HIF-1a-specific RNAi lentiviral vectors and selected with blasticidin. Real-time PCR and wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 36 publications
4
40
0
Order By: Relevance
“…The mechanisms by which HIF-1 contributes to resistance are likely to be complex and varied depending on cell genotype. Indeed, recent data observing sensitisation to cisplatin using HIF-targeting RNAi suggest that reversal of hypoxic resistance is p53 dependent (Hao et al, 2008). We previously reported that HIF-1 can alter the balance of pro-and antiapoptotic proteins under hypoxic conditions (Erler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which HIF-1 contributes to resistance are likely to be complex and varied depending on cell genotype. Indeed, recent data observing sensitisation to cisplatin using HIF-targeting RNAi suggest that reversal of hypoxic resistance is p53 dependent (Hao et al, 2008). We previously reported that HIF-1 can alter the balance of pro-and antiapoptotic proteins under hypoxic conditions (Erler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…173 This may occur in part by suppressing glucose transporter-1 and vascular endothelial growth factor expression, 173 although other investigators have observed that suppression of HIF-1a will also affect the expression of Bcl-2 family members such as Bid. 174 Thus, targeting mTOR expression would influence the expression of HIF-1a and may prevent drug resistance.…”
Section: Mtorc1-hif Drug Resistancementioning
confidence: 99%
“…For example, Li et al (2006a,b) showed that the knockdown of HIF-1 α in breast carcinoma cells repressed G 0 /G 1 -phase accumulation and relieved S-phase block, thereby increasing sensitivity to chemotherapy and attenuating tumor growth (Li et al , 2006a,b ). Functional interference with HIF-1 α in various tumor cells has been shown to result in enhanced cell death upon treatment with chemotherapeutic agents (Ricker et al , 2004 ;Peng et al , 2006 ;Hao et al , 2008 ;Sermeus et al , 2008 ;Flamant et al , 2010 ). However, experimentally increasing HIF-1 α enhanced therapy resistance (Ji et al , 2006 ;Martinive et al , 2006 ).…”
Section: Targeting Hif To Improve Cancer Therapymentioning
confidence: 99%